2015
DOI: 10.1523/jneurosci.1164-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Prox1Regulates the Subtype-Specific Development of Caudal Ganglionic Eminence-Derived GABAergic Cortical Interneurons

Abstract: Neurogliaform (RELNϩ) and bipolar (VIPϩ) GABAergic interneurons of the mammalian cerebral cortex provide critical inhibition locally within the superficial layers. While these subtypes are known to originate from the embryonic caudal ganglionic eminence (CGE), the specific genetic programs that direct their positioning, maturation, and integration into the cortical network have not been elucidated. Here, we report that in mice expression of the transcription factor Prox1 is selectively maintained in postmitoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 130 publications
12
119
1
Order By: Relevance
“…LGE/CGE-derived interneurons express several neurochemical markers including VIP, RLN, NPY, and calretinin (Lee et al, 2010;Ma et al, 2012;Miyoshi et al, 2015). These molecules are expressed across all cortical layers.…”
Section: Differential Expressions Of Neurochemical Markers Between Lamentioning
confidence: 99%
See 3 more Smart Citations
“…LGE/CGE-derived interneurons express several neurochemical markers including VIP, RLN, NPY, and calretinin (Lee et al, 2010;Ma et al, 2012;Miyoshi et al, 2015). These molecules are expressed across all cortical layers.…”
Section: Differential Expressions Of Neurochemical Markers Between Lamentioning
confidence: 99%
“…Neocortical interneurons were originally thought to be derived from the LGE based on a genetic study (Anderson et al, 1997) and tracing studies using rat embryos injected with lipophilic dyes (de Carlos et al, 1996;Tamamaki et al, 1997). The interpretation of these results came into question with the findings that the MGE is an origin for interneurons (Lavdas et al, 1999;Sussel et al, 1999;Wichterle et al, 1999), that MGE-derived interneurons migrate through the LGE (Anderson et al, 2001;Wichterle et al, 2001), and that in vivo transplantation studies failed to show a LGE origin of cortical interneurons (Wichterle et al, 2001;Nery et al, 2002). Nevertheless, there are several lines of evidence consistent with the notion that the LGE gives rise to some cortical interneurons.…”
Section: Possible Origins Of Neocortical Interneurons Labeled In Groumentioning
confidence: 99%
See 2 more Smart Citations
“…5HT3aR is expressed in migrating and mature CGE-and POA-derived cells (Lee et al, 2010;Vucurovic et al, 2010) and is cell-autonomously required for the migration and positioning of RLN + INs in the neocortex (Murthy et al, 2014). Finally, SP8 and PROX1 are transcription factors expressed principally in subpopulations of lateral ganglionic eminence (LGE)/CGE-derived cortical INs (Ma et al, 2012;Rubin and Kessaris, 2013;Rudy et al, 2011) and a recent report has demonstrated a crucial role for PROX1 in the embryonic and postnatal acquisition of CGE-derived cortical IN properties (Miyoshi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%